Transmission rate variation among three B chromosome variants in the fish Prochilodus lineatus (Characiformes, Prochilodontidae) - Penitente, Manolo; Voltolin, Tatiana A.; Senhorini, Jose A.; Bortolozzi, Jehud; Foresti, Fausto; Porto-foresti, Fabio (Academia Brasileira de Ciências, 2013)
Estudos citogenéticos foram desenvolvidos em Prochilodus lineatus (Valenciennes 1836), os quais descrevem um interessante sistema de pequenos cromossomos supranumerários. O objetivo deste trabalho foi estudar a frequência e morfologia dos cromossomos B em indivíduos a partir da linhagem parental e os padrões de herança destes elementos em indivíduos obtidos a partir de cruzamentos controlados na espécie P. lineatus. A taxa de transmissão dos cromossomos B revelaram um kB=0,388 para o tipo acrocêntrico, kB=0,507 para o tipo metacêntrico e kB=0,526 submetacêntrico. Os resultados obtidos levantam hipóteses de que os cromossomos B do tipo acrocêntrico se encontram em fase de extinção, enquanto que os supranumerários do tipo metacêntrico e submetacêntrico encontram-se em fase de neutralização, seguindo uma taxa de transmissão Mendeliana.

Cytogenetic studies were developed in Prochilodus lineatus (Valenciennes 1836), describing an interesting system of small supernumerary chromosomes. The purpose of this work is to study the frequency and morphology of B chromosomes in individuals from the parental line and the inheritance patterns of these elements in individuals obtained from controlled crosses in the species P. lineatus. The transmission rate of B chromosomes revealed a kB=0.388 for the acrocentric type, a kB=0.507 for the metacentric type and a kB=0.526 for the submetacentric type. The obtained results raise hypothesis that B-acrocentric chromosomes are involved in an extinction process in this species, while the metacentric and submetacentric supernumerary elements comprises a neutral mechanism and follows a Mendelian transmission rate.
Keywords: cromossomos supranumerarios; cruzamentos controlados; curimbata; citogenetica; heranca; supernumerary chromosomes; controlled crosses; curimbata; cytogenetic; inheritance